Probing the conformational changes of in vivo overexpressed cell cycle regulator 6S ncRNA - Makraki, Eleni; Miliara, Sophia; Pagkalos, Michalis; Kokkinidis, Michael; Mylonas, Efstratios; Fadouloglou, Vasiliki E. (Frontiers in Molecular Biosciences, 2023)
The non-coding 6S RNA is a master regulator of the cell cycle in bacteria which binds to the RNA polymerase-σ70 holoenzyme during the stationary phase to inhibit transcription from the primary σ factor. Inhibition is reversed upon outgrowth from the stationary phase by synthesis of small product RNA transcripts (pRNAs). 6S and its complex with a pRNA were structurally characterized using Small Angle X-ray Scattering. The 3D models of 6S and 6S:pRNA complex presented here, demonstrate that the fairly linear and extended structure of 6S undergoes a major conformational change upon binding to pRNA. In particular, 6S:pRNA complex formation is associated with a compaction of the overall 6S size and an expansion of its central domain. Our structural models are consistent with the hypothesis that the resultant particle has a shape and size incompatible with binding to RNA polymerase-σ70. Overall, by use of an optimized in vivo methodological approach, especially useful for structural studies, our study considerably improves our understanding of the structural basis of 6S regulation by offering a mechanistic glimpse of the 6S transcriptional control.